IJTIHAD politik Muhammadiyah : politik sebagai amal usaha / editor Zuly Qodir, Achmad Nurmandi, M. Nurul Yamin. - Zuly Qodir; Achmad Nurmandi; Nurul Yamin, M. (Pustaka Pelajar, 2015)
xviii, 276 hlm. ; 21 cm